A Fulfillment Of Private Rights Post-Divorce According To A Compilation Of Islamic Law - Helma Widya; Hermansyah Alam (Sean Institute, 2024)
Fulfilling children's rights is an activity to guarantee the needs of life, protect and give children what they should get, namely the right to live, grow and develop, be cared for and cared for by their own parents. Therefore, every child has the right to have the same rights in front of their parents, there is no discrimination or discrimination. This paper discusses the fulfillment of hadhanah rights after divorce, which aims to find out how the provisions for children's rights are according to the compilation of Islamic law after divorce, how efforts are made to fulfill the hadhanah rights of minors after divorce according to the compilation of Islamic law and find out how the analysis of decision No. 2184/Pdt.G/2020/PA.Mdn. This type of thesis research uses normative legal research with a qualitative approach method, while the research method used is literature study.(library research)with data collection techniques using secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. That the author found in the trial several factors that caused custody of the child to fall to the biological father. The results of this research consist of several factors, namely that the child's mother left her child more than 1 year ago, the mother is currently living with another man and already has a child with that man, while the child's mother has not divorced from the child's father, and all this time the child has been in his father's care. So the panel of judges considers that it is in the interests of the child that the child's education and morals will be better maintained if he remains with his father. Here the author agrees with the judge's decision which states that custody of the child falls to the father. To strengthen the quality and capacity as well as the integrity of families with children, the government is obliged to provide services and training for parents and children.